Christian doctrines in Islamic theology - Thomas, David (David Richard), 1948- (History of Christian-Muslim relations, 2008)
By the tenth century Islamic theology had become an integrated system by which theologians constructed accounts of the nature of the world and God's relationship with it. This book shows how Muslim theologians in this period made use of Christian doctrines as examples of misguided thinking to help confirm the correctness of their own theology.